2015
DOI: 10.1155/2015/103512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Benzoate Preservative on Micronucleus Induction, Chromosome Break, and Ala40Thr Superoxide Dismutase Gene Mutation in Lymphocytes

Abstract: Sodium benzoate is food preservative that inhibits microbial growth. The effects of sodium benzoate preservative on micronucleus induction, chromosome break, and Ala40Thr superoxide dismutase gene mutation in lymphocytes were studied. Sodium benzoate concentrations of 0.5, 1.0, 1.5, and 2.0 mg/mL were treated in lymphocyte cell line for 24 and 48 hrs, respectively. Micronucleus test, standard chromosome culture technique, PCR, and automated sequencing technique were done to detect micronucleus, chromosome brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 10 publications
(11 reference statements)
1
51
0
6
Order By: Relevance
“…The chromosome aberrations that are induced in human lymphocytes by benzene may be similar to those reported when lymphocytes (Mpountoukas and others 2008;Zengin and others 2011;Mamur and others 2012;Pongsavee 2015), Chinese hamster cells (Abe and Sasaki 1977;Hasegawa and others 1984), or the bone marrow cells of mice (Mukherjee and others 1988) are exposed to sorbate and/or benzoate. However, not all such investigations of this nature have identified genotoxicity (Münzner and others 1990), and those that do detect it do so only when the sorbate or benzoate is used in high concentrations, or when sorbate is present together with nitrate (Mukherjee and others 1988).…”
Section: The Capacity Of Sorbate and Benzoate Preservatives To Promotsupporting
confidence: 70%
“…The chromosome aberrations that are induced in human lymphocytes by benzene may be similar to those reported when lymphocytes (Mpountoukas and others 2008;Zengin and others 2011;Mamur and others 2012;Pongsavee 2015), Chinese hamster cells (Abe and Sasaki 1977;Hasegawa and others 1984), or the bone marrow cells of mice (Mukherjee and others 1988) are exposed to sorbate and/or benzoate. However, not all such investigations of this nature have identified genotoxicity (Münzner and others 1990), and those that do detect it do so only when the sorbate or benzoate is used in high concentrations, or when sorbate is present together with nitrate (Mukherjee and others 1988).…”
Section: The Capacity Of Sorbate and Benzoate Preservatives To Promotsupporting
confidence: 70%
“…For example, Ishidate et al [23] detected chromosomal damage in Chinese hamster fibroblast cell line treated with SB in vitro and also observed inhibition of DNA synthesis in rat liver cells following application of 100 mg/mL of SB. Pongsavee [2] also studied the in vitro effects of SB on a human lymphocyte cell line and described evidence of serious DNA damage. According to his results, the MN formation increased proportionally to the applied SB concentration and the treatment duration.…”
Section: Embryonal/fetal Effectsmentioning
confidence: 99%
“…Pongsavee observed chromosome breakage to occur (sister chromatid separation and chromosome gaps) at a dose of 2.0 mg/mL of SB at 24-and 48-hour incubation time, which was not observed in control groups. Based on this evidence that SB triggers micronucleus formation and induces chromosome breaks, Pongsavee [2] suggested that this food additive agent has mutagenic and cytotoxic effects in lymphocytes.…”
Section: Embryonal/fetal Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical deterioration of fish or seafood is able to be controlled by different technologies such as Modified Atmosphere Packaging (MAP) (Debevere and Boskou ; Ozogul and others ), food additives such as chemical ones (Kroupova and others ), irradiation technology (Mbarki and others ) during cold storage condition. On the other hand, consumers or food suppliers prefer the use of different or alternative preservation technique by reason of the fact that the most of present preservation methods could have adverse effects on human health (Anand and Sati ; Pongsavee ; Sharma ). These demands and concerns have led researchers to find out novel techniques, so, currently, a great effort has been exerted to control quality changes in fish.…”
Section: Introductionmentioning
confidence: 99%